The statues that walked unraveling the mystery of Easter Island - Hunt, Terry L. (Free Press, 2011)
The monumental statues of Easter Island, gazing out in their imposing rows over the island?s barren landscape, have been a great mystery ever since the island was first discovered by Europeans. How could the ancient people who inhabited this tiny speck of land, the most remote in the vast expanse of the Pacific, have built such monumental works, and moved them from the quarry where they were carved to the coast? And if the island once boasted a culture sophisticated enough to have produced such marvelous edifices, what happened to that culture? The prevailing accounts of the island?s history tell a story of self-inflicted devastation: a glaring case of eco-suicide. But when Terry Hunt and Carl Lipo began carrying out archaeological studies on the island in 2001, they uncovered a very different truth: they show that the Easter Islanders were remarkably inventive environmental stewards, rich with lessons for confronting the daunting environmental challenges of our own time.--From publisher description.